Forest resources resilience and conflicts - Shit, Pravat Kumar; Pourghasemi, Hamid Reza; Adhikary, Partha Pratim; Bhunia, Gouri Sankar; Sati, Vishwambhar Prasad (Elsevier, 2021)
Forest Resources Resilience and Conflicts presents modern remote sensing and GIS techniques for mapping, monitoring, measuring, and modeling forest resources. The book provides an up-to-date critical analysis of the discourse surrounding forest resources and society, illustrating the relationship between forest resources and the livelihood of local people. The book is organized into five parts. Each chapter reviews current understanding, present research, and future implications. The book is a valuable resource for researchers and students in environmental science, especially those interested in forestry, geography, and remote sensing. Utilizing case studies and novel advances in geospatial technologies, this reference provides a timely synthesis of a rapidly growing field and stimulates ideas for future work, especially in light of sustainable development goals. The book presents the effective contribution of the forestry sector to population livelihoods through improved collection of forestry statistics that foster understanding and integration of the forestry sector in poverty reduction processes and the national economy to enhance its integration in national planning. It is a valuable resource for researchers and students in environmental science, especially those interested in forestry, geography, and remote sensing.-